Blockchain for Cyberphysical Systems - Dorri, Ali; Kanhere, Salil; Jurdak, Raja (Artech House information security and privacy series., 2020)
This exciting book will explore how Blockchain (BC) technology has the potential to overcome challenges in the current cyber-physical system (CPS) environment. BC is a timestamp ledger of blocks that is used for storing and sharing data in a distributed manner. BC has attracted attention from practitioners and academics in different disciplines, including law, finance, and computer science, due to its use of distributed structure, immutability and security and privacy. However, applying blockchain in a cyber-physical system (CPS) is not straightforward and involves challenges, including lack of scalability, resource consumption, and delay.This book will provide a comprehensive study on blockchain for CPS. CPS and the existing solutions in CPS and will outline the limitations are presented. The key features of blockchain and its salient features which makes it an attractive solution for CPS are discussed. The fundamental challenges in adopting blockchain for CPS including scalability, delay, and resource consumption are presented and described. Blockchain applications in smart grids, smart vehicles, supply chain; and IoT Data marketplaces are explored. The future research directions to further improve blockchain performance in CPS is also provided.